Entrepreneurial intentions in an emerging industry: an exploratory study. (2017) - Alonso, Abel Duarte; Alexander, Nevil
This exploratory study examines entrepreneurial intentions in the emerging craft brewing industry from the perspective of predominantly micro and small craft brewery owners/brewing masters through the lens of the theories of universal values and planned behaviour. In doing so, the study makes a contribution to the existing academic literature on entrepreneurial intentions, micro and small businesses, and craft brewing industry. A contribution is also made by refining the adopted theoretical frameworks to study craft brewing entrepreneurship. Employing content analysis and word association revealed that passion for the craft brewing industry, turning a hobby into a professional undertaking, and professional and lifestyle changes - as compared to financial rewards- are predominant reasons for being involved in this industry. Alignments between the findings and universal values and two of the three predicting intentions were noticed, demonstrating the applicability of these theoretical frameworks in the context of the industry under examination.